Drumbeat LP "Aftershocks" to a Failed Explosive Eruption at Tungurahua Volcano, Ecuador. Issue 16 (24th August 2020) - Butcher, S.; Bell, A. F.; Hernandez, S.; Calder, E.; Ruiz, M.; Mothes, P.
Abstract: Highly periodic, repetitive long‐period (LP) earthquakes, known as "drumbeats, " have been observed at a range of volcanoes, typically during the ascent of degassed magma. Accelerating rates of drumbeats have been reported before explosions and potentially offer forecasts of future activity. However, the broader phenomenology of drumbeats is poorly understood. Here we describe an episode of over 900 LP earthquakes recorded in November 2015 at Tungurahua Volcano, Ecuador, that we believe are associated with a failed explosion. Rates of LP drumbeats accelerated for 10 hr, consistent with an inverse Omori's law. Before any explosion occurred, seismicity decreased following Omori's law, over a further 6 days. Despite earthquake rates decelerating, amplitudes, spectral peaks, Q values, and periodicity remain constant, suggesting there is little change in the source process with time. We argue that the decelerating seismicity is a result of progressive reduction of gas flux, unable to provide sufficient overpressure for explosion. Plain Language Summary: When a volcano is erupting, small earthquakes from the volcano can be used to infer what internal processes may be occurring. Earthquakes that are very similar to one another and repeat at consistent intervals are known as drumbeat earthquakes. These are of interest in volcanic systems as it implies the earthquakes are generated by a single, repeating source. Previous studies of drumbeat earthquakes at Tungurahua Volcano, Ecuador, have described these earthquakes occurring closer together in time and accelerating up to an explosion. In this case, we identify a sequence of drumbeats where the rate accelerates and, without any explosion, decelerates again. We suggest these earthquakes are generated by gas flux which is slowing down. This gas originates beneath a plug at the top of the conduit. We use statistical models to estimate when the volcano may have exploded if the earthquakes had continued to accelerate and quantify the subsequent deceleration in earthquake rate. Key Points: An episode of accelerating and decelerating long‐period (LP) drumbeat earthquakes is identified at Tungurahua volcano, Ecuador Bayesian gamma point process analysis constrains mirrored sequences of Omori law accelerating and decelerating seismicity Waveforms examined by cross correlation and Q factor reveal a gas‐driven, repeating, single source, which failed to culminate in an eruption